2018
DOI: 10.9734/jammr/2018/45194
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Refractive Errors and Impact of Corrective Treatments on Adult Patients Seen at a Tertiary Health Institution in South-South Nigeria

Abstract: Materials and Methods: This was a cross-sectional, descriptive study of 650 consecutive patients aged 18 years and above who have been diagnosed with refractive errors. They were interviewed using pretested, interviewer-administered questionnaires made up of both open and closed ended questions. Data were gotten and analysed using Statistical Package for Social Sciences (SPSS) for IBM (version 20, SPSS Inc, Chicago, IL, USA) after due ethical clearance and informed consent. Results were displayed using descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…6,10,11,22 Moreover, as a member of the WHO's global eye health action plan 2014-19, there was a need to generate the evidence for the prevalence and the reasons of visual impairment and apply the costeffective strategies to achieve the goal of reduction in avoidable blindness by 25% by the end of 2019. 6,20 As observed in the current study's results, though a higher percentage of the population was found to have a positive perception towards spectacle wear, there is a scope for exploring and rectifying the factors contributing to having a negative perception. A prior study within Oman observed inadequate knowledge about the common ocular condition causing visual impairment among the Omani adult population, and a holistic approach is recommended to improve the national eye healthcare system output.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…6,10,11,22 Moreover, as a member of the WHO's global eye health action plan 2014-19, there was a need to generate the evidence for the prevalence and the reasons of visual impairment and apply the costeffective strategies to achieve the goal of reduction in avoidable blindness by 25% by the end of 2019. 6,20 As observed in the current study's results, though a higher percentage of the population was found to have a positive perception towards spectacle wear, there is a scope for exploring and rectifying the factors contributing to having a negative perception. A prior study within Oman observed inadequate knowledge about the common ocular condition causing visual impairment among the Omani adult population, and a holistic approach is recommended to improve the national eye healthcare system output.…”
Section: Discussionsupporting
confidence: 53%
“…19 In contrast to the negative perceptions observed in these studies, in a study conducted among the adult African population, 2.8% of the participants with refractive error preferred using spectacles because they caused an impression of intelligence among peers. 20 The current fashion trends were also observed to be responsible for spectacle wear. 20 In Felix and Ebenezer's study, 57.2% of the studied population believed that spectacles made the individual look professional.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…8 The acceptance of refractive services has been demonstrated to be significantly influenced by lack of knowledge, stigma, and irrational beliefs about refractive problems across many continents. 10 The study of knowledge and attitude in a population is crucial for reducing this impact through early diagnosis and the referral of schoolchildren to eye care services by school teachers. 5 The act of wearing the recommended eyewear correction on a regular basis is referred to as compliance with spectacles.…”
Section: Introductionmentioning
confidence: 99%